Development of Practicum Module of Basic Physics 1 Integrated Version of The Qur'an - Permana, Imam; Moh. Wayong,; Hartini, (Al-Khazini: Jurnal Pendidikan Fisika, 2022)
This type of research is research and development (R&D) with a 4D development model consisting of the stages of definition, planning, development, and dissemination. This study aims to describe the steps for developing the basic physics practicum module 1 integrated with the verses of the Qur'an and to determine the feasibility level of the basic physics practicum module 1 integrated with the verses of the Qur'an in terms of the level of validity, practicality, and effectiveness. The research instruments used were validation sheets, observation sheets, and learning outcomes test questions. The data was then analyzed using descriptive statistics. The results showed that the module met the valid criteria with an average value of 0.91. The practicality level of the observation data shows a very practical and practical response with a percentage of 93.4%. The effectiveness is based on the learning outcomes test with the percentage of learning outcomes completeness 90%. Based on these data, it can be concluded that the integrated basic physics 1 practicum module or the Qur'an developed has the categories of validity, practicality, and effectiveness.